State of air quality in and outside of hospital wards in urban centres – a case study in Lahore, Pakistan - Gulshan, T.; Ali, Z.; Zona, Z.; Ansari, B.; Ahmad, M.; Zainab, M.; Nasir, Zaheer A.; Colbeck, I. (Pakistan Agricultural Scientists Forum, 2015)
Particulate pollution in healthcare facilities is a potential threat to healthcare workers, patients and visitors. A study was carried out to monitor particulate levels in and outside of five wards of Sheikh Zayed Hospital, a tertiary healthcare facility of Lahore. Measurements indicated that the hourly mean concentrations of PM2.5 in a medical, pulmonology (chest), surgical, pediatric and nephrology ward were 78 ± 37, 86 ± 46, 94 ± 48, 169 ± 122 and 488 ± 314 µg m- 3 respectively. The outside levels of PM2.5 of the same wards were 69 ± 27, 81 ± 49, 178 ± 85, 282 ± 164 and 421 ± 240 µg m- 3 . Indoor levels were higher than outdoors in all the wards except surgical and pediatric ward. Such elevated levels of PM can result in aggravation of the poor health status of the patients as well as affecting the hospital staff and visitors.
Keywords: particulate matter; hospital; wards; outdoor; Pakistan